O impacto da internet no modelo de negócio dos criadores e distribuidores de conteúdo da indústria fonográfica - Abreu Junior, Odair Froes de (2011)
Industries suffering transformations over time by several factors, among them are: the political, social, economic ones, so the radical innovations. It changes the way businesses are structured and that industry do business. Consequently, companies change their business models so they can seize the opportunities and minimize the problems derived from this transformation. Among the innovations that caused transformation in business models of many industries there is Internet. An industry that has strong impact of the Internet from product design to the various links of its supply chain was the Cultural. Among the cultural industries there is Phonographic Industry which is the object of the present study. In this context, this research aims to answer the question: "How the business model of content creators and distributors of the music industry was transformed by the use of the Internet, seen as an innovation." For this exploratory research was undertaken using the method of multi-case studies, where respondents were fourth content creators (composers, musicians, etc.) And two content distributors (record companies, music labels etc.) that use Internet as a business tool. Data collected by field survey were analyzed using the technique of content analysis. The conclusion, based on evidence found by analyzing the data, was that the Internet enabled content creators to reach their public directly without the intermediation of the content distributors. Thus creating an unprecedented access to these designers. While the content distributors are using the Internet intensively to disseminate and distribute their products. It was observed that the volume of sales of music on digital media grows rapidly every year, in contrast to the music in the holder physical that has a decline in trading volume.